VO2max characteristics of elite female soccer players, 1989-2007 - Haugen, T. A.; Tonnessen, E.; Hem, E.; Leirstein, S.; Seiler, S. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To quantify VO2max among female competitive soccer players as a function of performance level, field position, and age. In addition, the evolution of VO2max among world-class players over an 18-y period was quantified. Methods: Female players (N = 199, 22 ± 4 y, 63 ± 6 kg, height 169 ± 6 cm), including an Olympic winning squad, were tested for VO2max at the Norwegian Olympic Training Center between 1989 and 2007. Results: National-team players had 5% higher VO2max than 1st-division players (P = .042, d = 0.4), 13% higher than 2nd-division players (P < .001, d = 1.2), and 9% higher than junior players (P = .005, d = 1.0). Midfielders had 8% higher VO2max than goalkeepers (P = .048, d = 1.1). No significant differences were observed across outfield players or different age categories. There was a trend toward lower relative VO2max across time epochs. Conclusions: This study demonstrated that VO2max varies across playing-standard level in women`s soccer. No significant differences in VO2max were observed across outfield positions and age categories. Over time, there has been a slight negative development in VO2max among elite Norwegian soccer players.